2020
DOI: 10.2147/rmhp.s277657
|View full text |Cite
|
Sign up to set email alerts
|

<p>Factors Associated with Episiotomy Practices in Bahirdar City, Ethiopia: A Cross-Sectional Study</p>

Abstract: Background Episiotomy is the surgical enlargement of the vaginal orifice during the last part of the second stage of labor or childbirth by an incision to the perineum. The World Health Organization advises the use of episiotomy on a restricted and selective basis. Indeed, the rate of episiotomy in developed countries is decreasing, but in developing countries, including Ethiopia, it still remains high. Therefore, this study tried to assess the proportion and factors associated with episiotomy amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 23 publications
3
20
1
Order By: Relevance
“…Fetal macrosomia is common in obstetrics with problems in both the mother and newborn. The current review also showed that newborn birth weight ≥4,000 g was another risk factor associated with the practice of episiotomy compared with normal birth weight, which coincides with the findings reported in studies carried out in Ethiopia (53,54,57), France (51), and Nigeria (42,56,82). Other than newborns' , fetal macrosomia causes maternal complications during delivery, such as 3rd or 4th degree perineal tears (97,98).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Fetal macrosomia is common in obstetrics with problems in both the mother and newborn. The current review also showed that newborn birth weight ≥4,000 g was another risk factor associated with the practice of episiotomy compared with normal birth weight, which coincides with the findings reported in studies carried out in Ethiopia (53,54,57), France (51), and Nigeria (42,56,82). Other than newborns' , fetal macrosomia causes maternal complications during delivery, such as 3rd or 4th degree perineal tears (97,98).…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, the lowest rate of episiotomy, 9.3%, was reported in a study from Nigeria ( 40 ). In this meta-analysis, 17 of the 21 studies reported a percentage of episiotomy practice in primiparous and multiparous women ( 40 – 42 , 45 , 46 , 53 , 54 , 56 – 58 , 61 , 63 – 66 , 69 , 83 ), while the other four studies did not ( 55 , 82 , 84 , 85 ). The mean age of the study participants was not reported in ~66.7% of the studies ( 40 , 46 , 55 , 56 , 58 , 63 , 64 , 66 , 69 , 82 – 84 ).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This group encompassed three studies. 25 , 30 , 33 Women with prolonged SSOL have 9.31 times (OR: 9.31, 95% CI: 5.34, 16.22) higher risk of episiotomy practice than those with a normal duration of SSOL. In this meta-analysis, included studies have some heterogeneity I 2 = 36.03%, p = 0.208.…”
Section: Resultsmentioning
confidence: 99%